Adherence to the Mediterranean diet and risk of gastric cancer: a systematic review and dose–response meta-analysis - Zhu, Qin; Shu, Long; Zhou, Feng; Chen, Li-Peng; Feng, Yu-Liang (Frontiers in Nutrition, 2023)
Background: Despite growing evidence for the association of adherence to the Mediterranean diet with gastric cancer risk, the results remain inconclusive. The purpose of this systematic review and meta-analysis was to summarize the evidence from previous observational studies and assess the potential association between adherence to the Mediterranean diet and risk of gastric cancer using a dose-response meta-analysis. Methods: A comprehensive literature search for all observational studies published up to June 30, 2023 was conducted using the databases of PubMed, ISI Web of Science, EBSCO, China National Knowledge Infrastructure(CNKI) and Wanfang Data. The pooled relative risks(RRs) and 95% confidence intervals(CIs) were calculated for the highest versus the lowest categories of Mediterranean diet score in relation to gastric cancer risk, using random-effects models. The Cochran’s Q test and I-squared(I2) statistic were used to detect the sources of heterogeneity among the included studies. Results: Overall, eleven studies(five cohort and six case-control studies) with a total number of 1,366,318 participants were included in the final analysis. Combining 14 effect sizes from 11 studies revealed that compared with the lowest category, the highest adherence to the Mediterranean diet was associated with a 29% reduction in the risk of gastric cancer(RR:0.71; 95%CI:0.59-0.84, P<0.001). In addition, linear dose-response analysis showed that each 1-score increment in Mediterranean diet score was associated with a 5% lower risk of gastric cancer(RR:0.95; 95%CI: 0.94-0.96, P<0.001). Stratified analysis showed a significant association between adherence to the Mediterranean diet and risk of gastric cancer in case-control studies(RR=0.44;95%CI:0.32-0.61, P<0.001), and a marginally significant association in prospective cohort studies(RR=0.88; 95%CI: 0.79-0.98, P=0.024), respectively. At the same time, a more significant association between Mediterranean diet and reduced risk of gastric cancer was observed in other countries(RR=0.28; 95%CI:0.16- 0.49, P<0.001) than in Western countries(RR=0.75; 95%CI:0.64-0.88, P=0.001).Conclusions: Our results demonstrate that high adherence to the Mediterranean diet is associated with 29% reduced risk of gastric cancer. Further large prospective studies and randomized controlled trials are warranted to confirm our findings.